A Phase 1 Randomized Study of Single Intravenous Infusions of the Novel Nitroxyl Donor BMS‐986231 in Healthy Volunteers - Cowart, Douglas; Venuti, Robert P.; Lynch, Kim; Guptill, Jeffrey T.; Noveck, Robert J.; Foo, Shi Yin (Journal of clinical pharmacology, 2019)
Nitroxyl (HNO) is a reactive nitrogen molecule that has potential therapeutic benefits for patients with acute heart failure. The results of the first‐in‐human study for BMS‐986231, a novel HNO donor, are reported. The aim of this sequential cohort study was to evaluate the safety, tolerability, and pharmacokinetic profile of BMS‐986231 after 24‐ and 48‐hour intravenous infusions in healthy volunteers. Eighty subjects were randomized and dosed. Seven cohorts (stratum A) received BMS‐986231 0.1, 0.33, 1, 3, 5, 10, and 15 μg/kg/min or placebo, infused over 24 hours. An additional cohort (stratum B) received 10 μg/kg/min or placebo, infused over 48 hours. Adverse events (AEs) were reported for 30 days after completion of infusion. Blood/urine samples were collected at regular intervals; other parameters (blood pressure, heart rate/rhythm, cardiac index) were also assessed. Headaches were the most commonly reported drug‐related AE (48%) in those who received BMS‐986231, although their severity was reduced by hydration. No other significant drug‐related AEs were noted. BMS‐986231 was associated with dose‐dependent and well‐tolerated reductions in systolic and diastolic blood pressure versus baseline; cardiac index, as measured noninvasively, was increased. BMS‐986231 had no clinically significant effect on heart rate/rhythm or laboratory parameters. Its mean elimination half‐life was 0.7‐2.5 hours. BMS‐986231 was safe and well‐tolerated for up to 24 hours (15 μg/kg/min) or 48 hours (10 μg/kg/min), with a favorable hemodynamic profile observed. Ongoing studies continue to evaluate the potential benefit of BMS‐986231 in patients with acute heart failure.